The addition of apocalyptic theology in the dialogue section of the Book of Job - Santoso, Agus (HTS teologiese studies, 2025)
This study examines the presence of apocalyptic theology in the dialogue section of the Book of Job, with a particular focus on Job 19:25–27. The key terms ‘redeemer’ (גֹּאֵל, go‘el) and ‘witness’ (עֵד, ‘ed) have been the subject of extensive scholarly debate, particularly regarding their implications for Job’s hope. This article analyses the Hebrew text and its literary context to determine whether these terms convey an expectation of divine vindication, resurrection or ultimate justice. Rather than centring on interpretations alone, the study investigates the linguistic and theological dimensions of these words to clarify their role in Job’s discourse. Through a comparative analysis of biblical and ancient Near Eastern sources, this research explores the extent to which apocalyptic motifs emerge within Job’s speech. Contribution: This study contributes to the broader discussion of Job’s theological outlook by demonstrating how elements of apocalyptic thought are embedded in his expressions of hope. It also reassesses the function of Job’s go‘el and ‘ed within the framework of divine justice, moving beyond traditional legal and social interpretations. By situating Job’s language within the development of biblical eschatology, this research provides a fresh perspective on the portrayal of suffering, vindication and ultimate restoration in the Old Testament.